Birth in Hard Times When You Belong To Minorities - Paola Bertoli; Veronica Grembi; The Linh Bao Nguyen (Global Labor Organization (GLO), 2020)
Combining a unique dataset of birth records with municipal-level real estate infor- mation, we assess the impact of the 2008 recession on the health of immigrant newborns in Italy. Health at birth (e.g., low birth weight) of immigrants deteriorated more than health at birth of Italians. The negative effects on immigrants are not equally dis- tributed across ethnicities, but rather they are driven by the main economic activity of the ethnicity and its related network at the municipal level. Immigrants whose ethnicity is mainly employed in the sectors most affected during the recession, suffered the most. By contrast, the recession hardship is mitigated for immigrants in municipalities where their ethnic network is organized through more registered immigrant associations. The characteristics of ethnic groups and their organization at the municipal level do not explain the heterogeneous effects on Italian newborns and this confirms network rather than neighborhood effects.
Keywords: I1; I12; J15; J60; 330; Recessions; Immigrants; Low birth weight; Premature babies; Networks